Islamic bond announcement: The relationship between Islamic debt characteristics and stock return - Fauzi, Fitriya; Basyith, A.; Locke, S.; Foo, D. (2015)
This study attempts to examine whether Islamic debt characteristics, Islamic debt issuance frequency, Islamic debt type, and firm performance create a wealth effect to shareholders and/or investors when issuing Islamic debt. Using a quarterly balanced panel of 80 Malaysian firms and 20 Indonesian firms issuing Islamic debt which spans from 2000 to 2009; this study employs a the generalised least square (GLS) and the ordinary least square (OLS) for Malaysian and Indonesian data respectively for robustness according to specification testing results. The findings for Islamic debt characteristics' impact on stock return reveal that the Islamic debt characteristics, which are debt to equity ratio and firm size, have a positive and significant impact on shareholder wealth, while Islamic debt offering size and maturity have no significant impact on shareholders' wealth for Malaysia. For Indonesia, the result is similar to the result obtained for Malaysia except for debt equity ratio and firm size which have positive and significant impacts. With regards to the frequency and types of Islamic debt issued, only the first issuance of Islamic debt and Islamic debttypes have a positive and significant impact on shareholders' wealth for Malaysia and Indonesia, with exception that there is no debt-type for Indonesia. In terms of the firm value and/or firm financial performance; higher firm value or firm financial performance of firms issuing Islamic debt has a positive and significant impact on shareholders' wealth for Malaysia and Indonesia. IJER